Transformation of Islamic Education Management in The Era of Society 5.0 - Muhammad Alawilhuda; Muhammad Fajrin Alfadilah; Zaini Miftah (Yayasan Mutiara Hati Moeslem, 2025)
The transformation of student management in Islamic educational institutions is a crucial necessity in facing the era of Society 5.0, which is characterized by the integration of advanced technologies such as Artificial Intelligence (AI), the Internet of Things (IoT), and big data. These developments affect various aspects of life, including education, which is currently challenged by the lack of technological adaptation in student management and the continued use of conventional teaching methods. This study aims to explore innovative strategies to optimize student management in order to enhance the quality of Islamic education in alignment with contemporary developments. The research method used is library research with a descriptive qualitative approach, collecting data through analysis of various literature sources, including journals, articles, and books relevant to the transformation of Islamic education and technology in the Society 5.0 era. The findings indicate that technology integration can improve the efficiency, accuracy, and quality of educational services. It enables better student data management, personalized learning, and data-driven decision-making. Moreover, the use of analytical tools and digital platforms supports more interactive and engaging learning processes. However, this transformation requires strong support from competent educators, adequate facilities, and a balanced approach between modern technology and Islamic values. This study emphasizes the importance of innovation in student management to address the challenges of Society 5.0 without compromising the identity of Islamic education. The implementation of technology-based strategies is expected to improve the quality of Islamic education while shaping a generation that is adaptive, competent, and morally upright.